2015
DOI: 10.1016/j.jvir.2014.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combination Therapies in the Management of Hepatocellular Carcinoma: Transarterial Chemoembolization with Radiofrequency Ablation versus Microwave Ablation

Abstract: Purpose To compare retrospectively the outcomes and complications of transcatheter arterial chemoembolization with drug-eluting embolic agents combined with radiofrequency (RF) ablation or microwave (MW) ablation in treatment of hepatocellular carcinoma (HCC). Materials and Methods From 2003–2011, 89 patients with HCC received a combination therapy—transcatheter arterial chemoembolization plus RF ablation in 38 patients and transcatheter arterial chemoembolization plus MW ablation in 51 patients. Local tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 17 publications
4
25
1
4
Order By: Relevance
“…Virk et al retrospectively demonstrated similar marginally superior results with respect to initial response and local recurrence in those treated with MWA ablation and neoadjuvant TACE (25). Ginsburg et al showed comparable initial local response and progression free survival in their retrospectively analyzed RFA/TACE and MWA/TACE cohorts (26). Both studies reinforce our central hypothesis that MWA is at least as effective as RFA and should be given credence in the national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Virk et al retrospectively demonstrated similar marginally superior results with respect to initial response and local recurrence in those treated with MWA ablation and neoadjuvant TACE (25). Ginsburg et al showed comparable initial local response and progression free survival in their retrospectively analyzed RFA/TACE and MWA/TACE cohorts (26). Both studies reinforce our central hypothesis that MWA is at least as effective as RFA and should be given credence in the national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data comparing different combined embolization and ablation strategies. One recent study showed similar safety and efficacy when comparing TACE-RF and TACE-MW for the treatment of HCC (43). …”
Section: Current Literature On Treating Primary and Secondary Liver Cmentioning
confidence: 97%
“…The 1-, 3-, and 5-year disease-free survival rates were 70.5%, 42.3%, and 34.2%, respectively, for the RFA group and 62.3%, 33.8%, and 20.8% for the microwave ablation group; even in this case no statistically significant difference was noted. Interestingly, for the subgroup of patients with tumor diameters of 3.1-5.0 cm, the disease-free survival curve for the RFA-treated group was (33). Eighty-nine patients with HCC received TACE plus RFA (38 patients) or TACE plus microwave ablation (51 patients), without any statistically significant difference between the two groups in patient demographics, including age, sex, and etiology of liver cirrhosis, and no significant difference in tumor characteristics, including tumor size, number of tumors, and BCLC staging.…”
Section: Ablative Therapies: Radiofrequency Ablation (Rfa) -Percutanementioning
confidence: 98%